2014
DOI: 10.1111/cei.12293
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota and faecal transplantation as treatment modality for insulin resistance and type 2 diabetes mellitus

Abstract: SummaryThe prevalence of obesity and diabetes mellitus type 2 is increasing rapidly around the globe. Recent insights have generated an entirely new perspective that the intestinal microbiota may play a significant role in the development of these metabolic disorders. Alterations in the intestinal microbiota composition promote systemic inflammation that is a hallmark of obesity and subsequent insulin resistance. Thus, it is important to understand the reciprocal relationship between intestinal microbiota comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 50 publications
1
53
0
2
Order By: Relevance
“…Among the individual genera which responded to the dietary intervention, the abundance of Faecalibacterium was directly related to the concentration of butyric acid, as suggested by the positive association between changes in butyrate concentration and the abundance of Faecalibacterium. A study using faecal microbiota transplantation from lean donors to insulin-resistant patients with metabolic syndrome demonstrated that faeces from lean subjects were associated with enhanced numbers of butyrate-producing bacteria and increased insulin sensitivity 41. In contrast, a significant reduction of dietary carbohydrates in omnivores led to much lower levels of faecal SCFAs and decreased bacterial numbers 39.…”
Section: Discussionmentioning
confidence: 99%
“…Among the individual genera which responded to the dietary intervention, the abundance of Faecalibacterium was directly related to the concentration of butyric acid, as suggested by the positive association between changes in butyrate concentration and the abundance of Faecalibacterium. A study using faecal microbiota transplantation from lean donors to insulin-resistant patients with metabolic syndrome demonstrated that faeces from lean subjects were associated with enhanced numbers of butyrate-producing bacteria and increased insulin sensitivity 41. In contrast, a significant reduction of dietary carbohydrates in omnivores led to much lower levels of faecal SCFAs and decreased bacterial numbers 39.…”
Section: Discussionmentioning
confidence: 99%
“…This research implicates enteric butyrate-producing bacteria, such as R. intestinalis , Faecalibacterium spp. and Eubacterium hallii, as potential probiotics for the alleviation of metabolic endotoxemia-induced T2D 223. There is also evidence that more classical probiotics, such as the commercial probiotic cocktail VSL#3, can offer complete correction of weight gain and glucose intolerance associated with diet-induced T2D in mice 224.…”
Section: Probiotics As Diabetic Therapiesmentioning
confidence: 99%
“…Positive benefits on satiety, cholesterol levels, and glucose metabolism have been recorded by increasing SCFA production in animals fed resistant starch [155,156]. The positive effects of butyrate-producing bacteria on blood glucose and lipid metabolism are also evidenced by fecal transplantation studies [157,158]. The positive effects on glucose are achieved largely by increases in glucagon-like peptide-1, which increases insulin secretion, lowering plasma glucose and preserving beta cell function [159,160].…”
Section: Effects Of Scfas On Energy Homeostasismentioning
confidence: 99%